Control over crystal size in vapor deposited metal-halide perovskite films - Lohmann, KB; Patel, JB; Rothmann, MU; Xia, CQ; Oliver, RDJ; Herz, LM; Snaith, HJ; Johnston, MB; Johnston, MB (American Chemical Society (ACS), 2020)
Understanding and controlling grain growth in metal halide perovskite polycrystalline thin films is an important step in improving the performance of perovskite solar cells. We demonstrate accurate control of crystallite size in CH3NH3PbI3 thin films by regulating substrate temperature during vacuum co-deposition of inorganic (PbI2) and organic (CH3NH3I) precursors. Films co-deposited onto a cold (−2 °C) substrate exhibited large, micrometer-sized crystal grains, while films that formed at room temperature (23 °C) only produced grains of 100 nm extent. We isolated the effects of substrate temperature on crystal growth by developing a new method to control sublimation of the organic precursor, and CH3NH3PbI3 solar cells deposited in this way yielded a power conversion efficiency of up to 18.2%. Furthermore, we found substrate temperature directly affects the adsorption rate of CH3NH3I, thus impacting crystal formation and hence solar cell device performance via changes to the conversion rate of PbI2 to CH3NH3PbI3 and stoichiometry. These findings offer new routes to developing efficient solar cells through reproducible control of crystal morphology and composition.